EDUCATION IN UZBEKISTAN (Archive of Conferences, 2021)
Uzbek model of education. The system of education and training of personnel, which had developed before the proclamation of independence in Uzbekistan, absolutely did not correspond to the essence of the democratic reforms that began to be carried out in the republic. Fundamental reforms were also caused by the crisis in the world system that arose back in the 80s of the last century. A democratic and developing state headed by the president was well aware that hopes for the future were associated with the younger generation, therefore the head of state proposed a program to the people and society that would radically reform the entire education system